Discovery and therapeutic implications of bioactive dihydroxylated phenolic acids in patients with severe heart disease and conditions associated with inflammation and hypoxia. (November 2022) - Bai, Yajun; Jia, Pu; Zhao, Ye; Yang, Lingjian; Wang, Xiaoxiao; Wang, Xue; Wang, Jing; Zhong, Ni'er; Deng, Huaxiang; Du, Linxiang; Fang, Jiacheng; Xue, Yanbo; et al.
Abstract: Our initial studies detected elevated levels of 3, 4-dihydroxyphenyllactic acid (DHPLA) in urine samples of patients with severe heart disease when compared with healthy subjects. Given the reported anti-inflammatory properties of DHPLA and related dihydroxylated phenolic acids (DPAs), we embarked on an exploratory multi-centre investigation in patients with no urinary tract infections to establish the possible pathophysiological significance and therapeutic implications of these findings. Chinese and Caucasian patients being treated for severe heart disease or those conditions associated with inflammation (WBC ≥ 10 ×10 9 /L or hsCRP ≥ 3.0 mg/L) and/or hypoxia (PaO2 ≤ 75 mmHg) were enrolled; their urine samples were analyzed by HPLC, HPLC-MS, GC-MS and biotransformation assays. DHPLA was detected in urine samples of patients, but undetectable in healthy volunteers. Dynamic monitoring of inpatients undergoing treatment showed their DHPLA levels declined in proportion to their clinical improvement. In DHPLA-positive patients' fecal samples, Proteus vulgaris and P. mirabilis were more abundant than healthy volunteers. In culture, these gut bacteria were capable of reversible interconversion between DOPA and DHPLA. Furthermore, porcine and rodent organs were able to metabolize DOPA to DHPLA and related phenolic acids. The elevated levels of DHPLA in these patients suggest bioactive DPAs are generated de novo as part of a human's defense mechanism against disease. Because DHPLA isolated from Radix Salvia miltiorrhizae has a multitude of pharmacological activities, these data underpin the scientific basis of this medicinal plant's ethnopharmacological applications as well as highlighting the therapeutic potential of endogenous, natural or synthetic DPAs and their derivatives in humans. Graphical Abstract: ga1